Thinking and feeling about novelty: How cognition and emotion shape investment in novel ideas - Mount, Matthew P.; Le, Henry Tue; Bowman, Gary; Golding, Christopher (Strategic Management Journal, 2026)
Abstract While prior research on the strategic framing of innovation highlights the cognitive mechanisms underlying novelty evaluation, we know little about the corresponding emotional mechanisms. Drawing on appraisal theory, construal level theory, and the literature on emotions, we theorize two distinct appraisal‐emotion pathways through which the framing of novel ideas evokes hope and awe among investors with different motives. We argue that high‐construal framing supplements economically motivated investors' low‐level feasibility orientation, which evokes hope and increases their willingness to invest. By contrast, low‐construal framing supplements non‐economically motivated investors' high‐level desirability orientation, which evokes awe and increases their willingness to invest. We test and find some support for these within‐motive pathways across three studies. Our study offers new theoretical and practical insights on the strategic framing of novel ideas.